Acute Stroke Biomarkers: Are We There Yet? - Dagonnier, Marie; Donnan, Geoffrey A.; Davis, Stephen M.; Dewey, Helen M.; Howells, David W. (Frontiers in Neurology, 2021)
Background: The distinction between stroke subtypes and knowledge of the time of stroke onset is critical in clinical practice. Thrombolysis and thrombectomy are very effective but selective treatment for ischaemic stroke. Neuroimaging can help decide who and how to treat but is expensive, has contra-indications and is not always readily available, contributing to disappointing under use of the existing therapies. Aim: An alternative approach to these problems is to identify blood biomarkers which reflect the body’s response to the damage caused by the different types of stroke. Specific blood biomarkers capable of differentiating ischemic stroke from haemorrhage and mimics, identifying large vessel occlusion and capable of predicting stroke onset time would expedite diagnosis and increase the number of patients eligible for reperfusion therapies. Summary of review: To date, measurements of candidate biomarkers have usually been performed later than the clinically relevant thrombolysis time window. Nevertheless, some candidate markers of brain tissue damage, particularly the highly abundant glial structural proteins like GFAP and S100β and the matrix protein MMP-9 offer promising results. Grouping of biomarkers in panels can offer additional specificity and sensitivity for ischemic stroke diagnosis. Unbiased ‘omics’ approaches have great potential for biomarker identification because of greater gene, protein and metabolite coverage but seem unlikely to be the detection methodology of choice because of their inherent cost. Conclusion: To date, despite the evolution of the techniques used in their evaluation, no individual candidate or multimarker panel has proven to have adequate performance for use in an acute clinical setting where decisions about an individual’s fate are being made. Timing of biomarker measurement, particularly early when decision making is most important, requires urgent and systematic study.